The Potential of Randai as an Educational Tourism Attraction Based on Experiential Learning in West Sumatra - Fadli, Muhammad; Fasandra, Fernando (Institut Seni Indonesia Padangpanjang, 2024)
As one of the traditional theaters of West Sumatra, randai has not been too interested as an intangible cultural product that has great potential to be developed as an attraction in the concept of edu-tourism. In contrast to piriang dance and silek which are more widely known, and are in demand by tourists to learn or as performances at tourist sites. This study aims to identify the potential of randai as an experiential learning-based edu-tourism attraction using qualitative methods. Data collection was carried out by means of observation, interviews and documentation. The results showed that in randai there are various moral lessons both exposed directly and through signs in its movements and formations. Randai becomes so complex as “raw material” that is worth processing in the concept of edu-tourism because this art combines role art, literary art, dance art, and music art at the same time. Making randai as part of a tourism product such as a tour package that offers experiental learning for tourists who come to West Sumatra.